A new theory to aid in judging power system transient stability - Cao,GY; Hill,DJ; Hui,R; Chen,C (Power System Technology, 2005)
Inspired by the concept of trajectory sensitivity of dynamic systems and based on the knowledge of domain of attraction and asymptotic stability of dynamic systems, the authors proposed a new principle that could be used to aid in judging power system transient stability. It could be known from this principle that whether an initial point lied in the domain of attraction of an equilibrium point of autonomous nonlinear dynamic systems or not was able to be decided by the asymptotic stability of equilibrium point of its linearized system, which had a lot of 'good' properties that could be exploited. A positive constant was defined as the acceleration factor of the linear system, which could accelerate the convergence or divergence of this system so as to decrease the simulation time of the power system dynamics for transient stability analysis. Results of applying the proposed principle to single-machine infinitive-bus system and multi-machine system show that this principle is correct and feasible.